2016
DOI: 10.1177/2325967115623212
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Superior Labral Tears Diagnosed by MRI in Middle-Aged Patients With Asymptomatic Shoulders

Abstract: Background:The incidence of superior labral surgery has increased in the past decade in the United States, and a contributing factor could be an increased rate of superior labral tears diagnosed with magnetic resonance imaging (MRI). Prior MRI studies of the asymptomatic shoulder have focused on rotator cuff pathology or pathology in a narrow and specific group of athletes. Labral abnormalities have not previously been thoroughly evaluated in asymptomatic middle-aged individuals.Purpose:To evaluate the prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
43
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 39 publications
4
43
1
1
Order By: Relevance
“…In the original series describing the Snyder classification [22], a large proportion of the original 27 patients were found to have concomitant shoulder disorders, and it is possible that the observed superior labral disorder could have been an incidental finding. A subsequent study showed a high prevalence of SLAP tears in asymptomatic middle-aged individuals [20].…”
Section: Limitationsmentioning
confidence: 96%
See 2 more Smart Citations
“…In the original series describing the Snyder classification [22], a large proportion of the original 27 patients were found to have concomitant shoulder disorders, and it is possible that the observed superior labral disorder could have been an incidental finding. A subsequent study showed a high prevalence of SLAP tears in asymptomatic middle-aged individuals [20].…”
Section: Limitationsmentioning
confidence: 96%
“…This may be partly attributable to the difficulty in understanding even normal superior labral anatomy and age-related changes that can occur [20]. The presence of a sublabral sulcus is not considered abnormal, yet our understanding regarding how to differentiate a normal sublabral foramen from a SLAP lesion is not well characterized or described.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cross-sectional studies have shown that there is a high prevalence of SLAP pathology identified in middle-aged patients with asymptomatic shoulders. 3 Given the high prevalence of this condition, diagnosing a SLAP tear (especially in middle-aged patients) as the isolated clinical entity attributable for shoulder dysfunction can be challenging especially because SLAP tears are often identified at surgery for patients with other painful shoulder conditions. In fact, there is considerable controversy as to whether SLAP tears are an actual clinical problem in middle-aged patients.…”
mentioning
confidence: 99%
“…Since then the classification has been expanded by others but it should be noted that Snyder’s classification was based on a traumatic initiating episode causing the lesion, which was only diagnosed on arthroscopy, and not a degenerative process which may be akin to the difference between an acute and degenerative tear of the rotator cuff. Indeed, it should be noted that up to 72% of patients between the ages of 45 and 60 years old were noted to have a SLAP lesion on MRI and were asymptomatic for the lesion, and therefore may be an age-related phenomenon 3. A cohort where no distinction is made between acute injury and degenerative SLAP lesions could possibly lead to a type II statistical error.…”
mentioning
confidence: 99%